2022
DOI: 10.1186/s12978-022-01387-w
|View full text |Cite
|
Sign up to set email alerts
|

Birth rate after major trauma in fertile-aged women: a nationwide population-based cohort study in Finland

Abstract: Background To date, only a few small studies have assessed the effects of major orthopedic traumas on the subsequent birth rate in fertile-aged woman. We assessed the incidences of traumatic brain injury (TBI) and fractures of the spine, pelvis, and hip or thigh and evaluated their association with the birth rate in fertile-aged woman. Methods In this retrospective register-based nationwide cohort study, data on all fertile-aged (15–44 years of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…These data add to the previous study on fertility rates following trauma by extending the period of follow-up after the trauma during which births were enumerated to provide a long-term estimate of fertility post-trauma. 15 These results have important consequences on public health policy decisions. For one, since fewer injured women are expected to give birth after their trauma, their risk of developing HDFN from receipt of an RhD-positive transfusion during their resuscitation is correspondingly lower.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data add to the previous study on fertility rates following trauma by extending the period of follow-up after the trauma during which births were enumerated to provide a long-term estimate of fertility post-trauma. 15 These results have important consequences on public health policy decisions. For one, since fewer injured women are expected to give birth after their trauma, their risk of developing HDFN from receipt of an RhD-positive transfusion during their resuscitation is correspondingly lower.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective analysis of all injured WCPs between the ages of 15-49 in Finland between 1998 and 2018 found that some women with pelvic fractures and hip or thigh fractures had lower probabilities of giving birth in the 5 years following their trauma compared to women with wrist fractures. 15 The goal of that study was to analyze the short-term effects of trauma on fertility, however, given the increasing mean age at which women give birth, it is also important to consider the long-term effects of trauma on fertility rates. 16 To this end, a study 15 involving two Finnish databases on births and health care was reanalyzed using the maximum length of follow-up that was possible to provide a more comprehensive estimate of their long-term post-injury fertility so that a more accurate fertility rate percentage can be used in risk calculations of HDFN following exposure to RhD-positive RBCs or LTOWB in trauma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the latest nationwide study on birth rates after traumas found that women with TBIs had a relatively high birth rate [ 1 ]. Even though TBIs are known to negatively affect the hypothalamic–pituitary complex and the endocrine system, especially the functions of gonadal hormones, [ 3 , 4 ] it appears that alterations to the hormonal system do not increase the risk for multifetal gestations.…”
Section: Discussionmentioning
confidence: 99%
“…A previous Finnish nationwide study on birth rates after different traumas found that women with pelvic or hip fractures had lower birth rates than women in the general population. However, those women who had sustained a TBI had an even higher birth rate than the control group [ 1 ]. To our knowledge, this is the first time the effects of TBI on the risk for having multifetal gestations has been studied.…”
Section: Introductionmentioning
confidence: 99%